Spectrum of pathogens in native liver, bile, and blood during pediatric liver transplantation. (5th March 2014) - Schukfeh, Nagoud; Doerner, Judith M.; Heintschel von Heinegg, Evelyn; Steinmann, Joerg; Metzelder, Martin L.; Kathemann, Simone; Hoyer, Peter F.; Paul, Andreas; Gerner, Patrick
Abstract During LTX, there may be a risk that pathogens of the native liver are released into the systemic circulation. No investigations on incidence/spectrum of pathogens in native livers have been published. We hypothesized that pathogens are found in the native liver of a large proportion of pediatric patients during LTX and investigated the microbiology of native livers. These data may help optimize antibiotic therapy. Twenty‐two consecutive pediatric patients (median age 14 months, range, 5 months–15 yr) receiving LTX in our department from October 2010 to October 2011 were included in this prospective study. Tissue and bile were collected from the explanted liver and were cultivated on different media. All liver tissues were investigated using a broad‐range PCR (SepsiTest®). In 16 patients, blood cultures were collected post‐transplantation. Eleven patients (50%) had at least one pathogen detected; nine of these patients had an underlying diagnosis of biliary atresia. SepsiTest® was positive in seven patients. In four patients it was the only test detecting any pathogen. In detail, the positivity rate for liver tissue in all patients was 41% (n = 9); for bile 25% (n = 3); and for blood 25% (n = 4). Thirteen different pathogens (69% bacterial, 31% fungal) were isolated. A highly‐sensitive broad‐range PCR appears to be an effective method to detect pathogens in native livers of patients undergoing LTX. A high number and variety of microbes, including a high proportion of fungal pathogens, were detected.